Positive electrode material, positive electrode sheet, and sodium-ion battery
Patent Information
- Application Number
- CN202310249128.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-03-15
AI Technical Summary
与锂离子电池三元正极类似,钠基层状氧化物具有较强的碱性,且由于钠盐比锂盐的碱性更强,极易受到水分影响而生产副产物,影响材料性能
[0080]本发明正极材料内核中的镍基氧化物具有高容量的特性,具有高的储钠容量,从而使得本发明正极材料具有较高的容量,提升了电池的综合性能,有利于构建高能量密度钠离子电池。
Smart Images

Figure CN116111083B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to cathode materials, cathode sheets, and sodium-ion batteries. Background Technology
[0002] Sodium-ion batteries have broad application prospects due to their high safety, abundant sodium resources, and low cost, and significant breakthroughs in industrial applications in recent years. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, primarily utilizing the intercalation and deintercalation of sodium ions between the positive and negative electrodes to achieve energy storage and release.
[0003] Currently, there are three main categories of materials that can be used as cathode materials for sodium-ion batteries: transition metal oxides, polyanionic compounds, and Prussian blue analogues. Among them, transition metal oxides have received widespread attention and research due to their high theoretical specific capacity and manufacturing process similar to that of ternary lithium-ion battery materials. Similar to ternary cathodes in lithium-ion batteries, sodium-based layered oxides are highly alkaline. Furthermore, because sodium salts are more alkaline than lithium salts, they are highly susceptible to moisture, producing byproducts that affect material performance. In addition, due to their strong alkalinity, they easily react chemically with binders during slurry preparation, leading to rapid slurry gelation and hindering subsequent processes such as coating, thus impacting battery production. Summary of the Invention
[0004] In view of this, the present invention provides a cathode material, a cathode sheet, and a sodium-ion battery. This cathode material can improve the stability of nickel-based oxides while ensuring high sodium storage capacity, which is beneficial for constructing high-energy-density sodium-ion batteries.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] This invention provides a cathode material having a core-shell structure, comprising a core and a shell, wherein the core comprises a nickel-based oxide as shown in Formula I:
[0007] Na x Ni a Fe b Mn c (M1) d O2 type I
[0008] Wherein, 0.7≤x≤1.0, 0<a<1, 0<b<1, 0<c<1, 0≤d<0.1; M1 is selected from one or more of Li, Mg, Zn, Co, Ca, Ba, Sr, Al, B, Cr, V, Zr, Ti, Sn, Mo, Ru, Si, Sb, Nb, and Te;
[0009] The shell contains Na, Cu, Fe, Mn, and O elements.
[0010] Preferably, the shell comprises a copper-based oxide as shown in Formula II:
[0011] Na y Cu i Fe j Mn k (M2) l O2 Type II
[0012] Wherein, 0.6≤y≤1.0, 0<i<1, 0<j<1, 0<k<1, 0≤l<0.1; M2 is independently selected from one or more of Li, Mg, Zn, Co, Ca, Ba, Sr, Al, B, Cr, V, Zr, Ti, Sn, Mo, Ru, Si, Sb, Nb, and Te.
[0013] The cathode material provided in this invention has a core-shell structure, with a nickel-based oxide core and a copper-based oxide shell. By setting the copper-based oxide coating layer, on the one hand, the stable characteristics of copper-based oxide in air and moisture environments can be utilized to improve the environmental stability of nickel-based oxide. This advantage is reflected in the improved stability of the slurry during performance testing. On the other hand, copper-based oxide also has the ability to store sodium, and its sodium storage potential is relatively high. This can improve the stability of nickel-based oxide while ensuring high sodium storage capacity and potential, which is beneficial for constructing high-energy-density sodium-ion batteries.
[0014] In the cathode material provided by this invention, when the core is not doped with M1 element, the general chemical formula of the nickel-based oxide is: Na x Ni a Fe b Mn c O2; When the core is doped with M1, the general chemical formula of nickel-based oxides is: Na x Ni a Fe b Mn c (M1) d O2, where 0.7≤x≤1.0, 0<a<1, 0<b<1, 0<c<1, 0≤d<0.1. Doping with M1 can improve the air stability and structural stability of the cathode material. This advantage is reflected in improved slurry stability and cycle stability, which is beneficial to improving the overall performance of the cathode material.
[0015] Preferably, 0.7 ≤ x ≤ 1.0, where x is any value among 0.7, 0.8, 0.9, and 1.0, or any value within any pairwise range of the above values.
[0016] Preferably, 0 < a < 1, and exemplarily, a is any value among 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.99, or any value between any two of the above-mentioned value ranges.
[0017] Preferably, 0 < b < 1, and b can be any value from 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 0.99, or any value between any two of the above ranges.
[0018] Preferably, 0 < c < 1, and c can be any value from 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99 or any value between any two of the above ranges.
[0019] Preferably, 0 ≤ d < 0.1, and d can be any value among 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.99, or any value between any two of the above ranges.
[0020] In the cathode material provided by this invention, when the shell layer is not doped with M2 element, the general chemical formula of the copper-based oxide is: Na y Cu i Fe j Mn k When O2 is doped with M2 element in the shell, the general chemical formula of copper-based oxides is: Na y Cu i Fe j Mn k (M2) l O2, where 0.6≤y≤1.0, 0<i<1, 0<j<1, 0<k<1, 0≤l<0.1. Doping with M2 can improve the air stability and structural stability of the cathode material. This advantage is reflected in improved slurry stability and cycle stability, which is beneficial to improving the overall performance of the cathode material.
[0021] Preferably, 0.6 ≤ y ≤ 1.0, and the exemplary x is any value among 0.6, 0.7, 0.8, 0.9, 1.0 or any value between any two of the above-mentioned value ranges.
[0022] Preferably, 0 < i < 1, and for example, i is any value among 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.99, or any value between any two of the above-mentioned value ranges.
[0023] Preferably, 0 < j < 1, and j can be any value from 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99 or any value between any two of the above ranges.
[0024] Preferably, 0 < k < 1, and k is any value among 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.99, or any value between any two of the above ranges.
[0025] Preferably, 0 ≤ l < 0.1, and l can be any value among 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.99, or any value between any two of the above ranges.
[0026] As a preferred choice, a, b, c, d, i, j, k, l satisfy the following relationship:
[0027] a+b+c+d=1, and / or, i+j+k+l=1.
[0028] Preferably, the median particle size D50 of the cathode material particles is 5–20 μm; exemplary values are any one of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20, or any value within any pairwise range of the above. With the cathode material particle D50 within this range, the cathode material can balance compaction and rate performance.
[0029] Preferably, the median particle size D50 of the cathode material particles is 5–16 μm;
[0030] Preferably, the median particle size D50 of the cathode material particles is 5–12 μm;
[0031] More preferably, the median particle size D50 of the cathode material particles is 5–10 μm.
[0032] Preferably, the D10 particle size of the cathode material particles is 0.5 to 5 μm, and more preferably, it is 1 to 3 μm. When the D10 of the cathode material particles is within this range, the cathode material can take into account both compaction and rate performance.
[0033] Preferably, the D90 particle size of the cathode material particles is 8–20 μm, and more preferably, it is 10–15 μm. When the D90 of the cathode material particles is within this range, the cathode material can take into account both compaction and rate performance.
[0034] Preferably, the shell thickness is 0.05–2 μm.
[0035] Preferably, the shell thickness is 0.1–1.5 μm. Within this range, the cathode material exhibits higher sodium storage capacity and specific capacity, thus improving the overall performance of the cathode material.
[0036] Preferably, the thickness of the shell layer is 1% to 30% of the radius of the cathode material particles; exemplary values are any one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 25%, and 30%, or any value within any pairwise range of the above values. Within this range, the coating layer of the copper-based material can effectively improve the environmental stability of the composite material and enhance its processing performance, which is beneficial for the preparation of cathode materials with high specific capacity and excellent processing performance. If the shell layer thickness exceeds this range, the overall specific capacity of the material will be lower due to the lower sodium storage capacity of the coating layer.
[0037] In this invention, particle diameter refers to the size of the particle. For spherical particles, it refers to the diameter of the sphere; for irregular particles, it refers to the maximum straight-line distance. The particle radius mentioned above refers to half the particle diameter.
[0038] Preferably, the thickness of the shell layer is 1% to 25% of the radius of the cathode material particles.
[0039] Preferably, the thickness of the shell layer is 1% to 20% of the radius of the cathode material particles;
[0040] In the embodiments provided by the present invention, the thickness of the shell layer is 1% to 12.5% of the radius of the positive electrode material particles.
[0041] In the embodiments provided by the present invention, the thickness of the shell layer is 1% to 6.25% of the radius of the cathode material particles.
[0042] More preferably, the thickness of the shell is 1% to 5% of the radius of the cathode material particles.
[0043] In the embodiments provided by the present invention, the thickness of the shell layer is 1% to 2.5% of the radius of the cathode material particles.
[0044] Preferably, the cathode material includes monocrystalline and / or polycrystalline materials.
[0045] In the embodiments provided by this invention, the cathode material exhibits two diffraction peaks at 2θ values of 40°–42.5° and 44°–46° in X-ray diffraction analysis. This characteristic indicates that the cathode material possesses relatively good crystallinity, which is beneficial for improving the structural stability of the material.
[0046] Preferably, no diffraction peak is observed at 2θ between 42.5° and 44°. In an embodiment of the invention, the Na shell... y Cu i Fe j Mn k (M2) l The O2 structure itself does not have a diffraction peak at 42.5°–44°, and the core Na x Ni a Fe b Mn c (M1) d The diffraction peaks of O2 at 42.5°–44° are relatively weak. Due to the covering of the shell, the diffraction peaks of the cathode material at 42.5°–44° disappear.
[0047] Preferably, the powder conductivity of the cathode material at a pressure of 50 MPa is 1.0E-07 to 1.0E-05 S / cm. Within this range, the powder conductivity ensures the electrical properties of the cathode material and improves its overall performance.
[0048] The present invention also provides a method for preparing the above-mentioned cathode material, comprising the following steps:
[0049] The composite precursor was obtained by co-precipitation method;
[0050] The composite precursor and sodium source are mixed and then sintered at high temperature to obtain the cathode material.
[0051] Preferably, the high-temperature sintering temperature is 700–1000℃ and the high-temperature sintering time is 10–40 h;
[0052] Preferably, the high-temperature sintering temperature is 800–900°C, and the high-temperature sintering time is 14–24 hours.
[0053] Preferably, the atmosphere for high-temperature sintering includes an air atmosphere, an air atmosphere with compressed air, or an oxygen atmosphere.
[0054] In the embodiments provided by the present invention, the method for preparing the positive electrode material includes the following steps:
[0055] (1) Mix soluble Ni salt, Fe salt, Mn salt and solvent, and add or not add soluble salt containing M1 element to obtain a first mixed solution; add complexing precipitant to the first mixed solution to obtain a first reaction solution; adjust the pH value of the first reaction solution to 9-12, and carry out a coprecipitation reaction at 40-80℃ to obtain a first coprecipitate;
[0056] (2) Mix soluble Cu salt, Fe salt, Mn salt, solvent, and the first coprecipitate, and add or not add soluble salt containing M2 element to obtain a second mixed solution; add complexing precipitant to the second mixed solution to obtain a second reaction solution; adjust the pH of the second reaction solution to 9-12, and carry out a coprecipitation reaction at 40-80℃ to obtain a composite precursor;
[0057] (3) The composite precursor and sodium source are mixed and sintered at high temperature and then ground to obtain the cathode material.
[0058] In the preparation process of the cathode material of the present invention, by comprehensively controlling the types of reactants, parameters of the co-precipitation reaction, types of product elements and doping amounts, the cathode material can have the specific chemical composition and structure of the present application, which can significantly improve the electrochemical performance of the cathode material, as well as improve the specific capacity, cycle performance, safety performance and energy density of sodium-ion batteries.
[0059] Preferably, the complexing precipitant includes, but is not limited to, one or more of hydroxides, carbonates, oxalates, and ammonia.
[0060] Preferably, the solvent is water and / or an organic solvent.
[0061] In the embodiments provided by the present invention, the solvent includes any one or a combination of at least two of the following: water, methanol, ethanol, acetone, propanol, isopropanol, ethylene glycol, n-butanol, cyclohexane, ethylenediamine, N-methylpyrrolidone, benzene, toluene, xylene, dimethyl ether, or diethyl ether.
[0062] Preferably, soluble Ni salts, Fe salts, Mn salts, Cu salts, soluble salts containing M1 element, and soluble salts containing M2 element can be sulfates, carbonates, acetates, chlorides, nitrates, etc.
[0063] Preferably, the sodium source is selected from any one or a combination of two or more of Na2CO3, NaHCO3, NaOH, Na2O, and CH3COONa.
[0064] The present invention also provides a positive electrode sheet, which includes the above-described positive electrode material and / or the positive electrode material prepared by the above-described preparation method.
[0065] Preferably, the positive electrode sheet includes a current collector and a positive electrode active material layer; the positive electrode active material layer is coated on the surface of the current collector; the positive electrode active material layer includes the aforementioned positive electrode material.
[0066] Furthermore, the positive electrode active material layer also includes a conductive agent and a binder.
[0067] Furthermore, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, or mixtures thereof. For example, carbon-based materials are selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof; metal-based materials are selected from metal powder, metal fiber, copper, nickel, aluminum, and silver.
[0068] Furthermore, the adhesive includes, but is not limited to, at least one of: sodium carboxymethyl cellulose, styrene-butadiene latex (styrene-butadiene rubber), polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene oxide.
[0069] Furthermore, the positive electrode sheet can be prepared according to conventional methods in the art. Typically, the positive electrode active material and optional conductive agents and binders are dispersed in a solvent (e.g., NMP) to form a uniform positive electrode slurry. The positive electrode slurry is then coated onto a current collector, and after drying and other processes, the positive electrode sheet is obtained.
[0070] The present invention also provides a sodium-ion battery, comprising the above-described positive electrode material and / or the positive electrode material prepared by the above-described preparation method, and / or the above-described positive electrode sheet.
[0071] In this invention, the application of sodium-ion batteries is not particularly limited and can be used for a variety of known applications. Examples include backup power supplies, automobiles, motorcycles, electric boats, bicycles, lighting fixtures, toys, power tools, large household batteries, and energy storage power stations.
[0072] The sodium-ion battery of the present invention further includes a negative electrode sheet, which includes a current collector and a negative electrode active material layer; the negative electrode active material layer is coated on the surface of the current collector; the negative electrode active material layer includes a negative electrode active material.
[0073] Furthermore, the negative electrode active material includes hard carbon.
[0074] Furthermore, the average particle size Dv50 of hard carbon is 5–15 μm. Within this range, the average particle size of hard carbon can improve the compaction of the electrode and reduce the sheet resistance. Moreover, when combined with a cathode containing this cathode material, it can result in a battery with superior overall performance.
[0075] Furthermore, the negative electrode active material layer also includes conductive agents, binders, and thickeners.
[0076] The range of types of conductive agents and binders that can be selected in the negative electrode active material layer is the same as that in the positive electrode active material layer.
[0077] Preferably, the thickener is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and carboxymethyl cellulose.
[0078] Furthermore, the negative electrode sheet can be prepared according to conventional methods in the art. Typically, the negative electrode active material and optional conductive agents and binders are dispersed in a solvent (e.g., water) to form a uniform negative electrode slurry. The negative electrode slurry is then coated onto a current collector, and after drying and other processes, the negative electrode sheet is obtained.
[0079] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0080] The nickel-based oxide in the core of the cathode material of this invention has high capacity characteristics and high sodium storage capacity, thereby enabling the cathode material of this invention to have high capacity, improving the overall performance of the battery, and facilitating the construction of high energy density sodium-ion batteries.
[0081] The core-shell composite oxide material provided by this invention combines the high capacity of nickel-based oxides with the high stability of copper-based oxides. While ensuring the high capacity of the composite material, the copper-based coating layer can improve the environmental stability of the composite material and enhance its processing performance. This facilitates the preparation of cathode materials with high specific capacity and excellent processing performance, greatly advancing the development of sodium-ion batteries. Attached Figure Description
[0082] Figure 1 A schematic diagram of the core-shell structure of a composite cathode material; where 1 represents the core and 2 represents the shell.
[0083] Figure 2 SEM and EDS images of the composite cathode material;
[0084] Figure 3 Example 1: XRD pattern of the composite cathode material;
[0085] Figure 4 XRD pattern of oxide cathode (without coating) in Comparative Example 1. Detailed Implementation
[0086] This invention discloses a cathode material, a cathode sheet, and a sodium-ion battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0087] Chemical element names in Chinese and English:
[0088]
[0089]
[0090] The reagents, instruments, and materials used in this invention can all be obtained through commercial channels.
[0091] The present invention will be further illustrated below with reference to the embodiments:
[0092] Preparation of sodium-ion batteries in Examples 1-3
[0093] I. Battery Structure
[0094] A battery consists of a positive electrode, a separator, a negative electrode, and an electrolyte;
[0095] The negative electrode includes a current collector and negative electrode active material layers disposed on both sides thereof;
[0096] The positive electrode includes a current collector and positive electrode active material layers disposed on both sides thereof; the positive electrode active material layers include the following positive electrode materials:
[0097] like Figure 1 As shown, the cathode material has a core-shell structure, with the shell layer located on the surface of the core; the core includes nickel-based oxide Na. x Ni a Fe b Mn c (M1) d O2, with a shell consisting of copper-based oxide Na y Cu i Fe j Mn k (M2) l O2, the general chemical formula of the positive electrode material is Na x Ni a Fe b Mn c (M1) d O2@Na y Cu i Fe j Mn k (M2) l O2. Where M1 or M2 is Al; 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 0.1, 0 < i < 1, 0 < j < 1, 0 < k < 1, 0 ≤ l < 0.1, a, b, c, d, i, j, k, l satisfy a + b + c + d = 1, i + j + k + l = 1, 0.7 ≤ x ≤ 1.0, 0.6 ≤ y ≤ 1.0.
[0098] The median particle size of the cathode material particles is 8–16 μm, and the thickness of the shell layer is 0.1–1.5 μm, which is 2.5%–25% of the radius of the cathode material particles.
[0099] See Table 1 for specific parameters.
[0100] II. Preparation Method
[0101] 1. Preparation of cathode materials
[0102] (1) First, soluble nickel sulfate, ferric sulfate, manganese sulfate, and aluminum nitrate containing Al (a soluble salt containing M1) are mixed according to their stoichiometric ratio and added to a solvent (deionized water, the same solvent below) to obtain a mixed solution, wherein the stoichiometric ratio of Ni / Fe / Mn is 1:1:1, and the stoichiometric ratio of Al is 22% of Fe; an appropriate amount of ammonia is slowly added to the mixed solution while stirring, and the pH value of the solution is 11.5±0.2, to obtain a coprecipitate containing Ni, Fe, Mn and M1; after filtration, it is washed with deionized water and set aside for later use;
[0103] (2) Subsequently, soluble copper sulfate, ferric sulfate and manganese sulfate are mixed in stoichiometric ratio and added to a solvent to obtain a mixed solution, wherein the stoichiometric ratio of Cu / Fe / Mn is 2:4:4; the precipitate prepared in step (1) is added, and after stirring and mixing evenly, an appropriate amount of ammonia water is added and stirring is maintained. The pH value of the solution is 11.5±0.2, and co-precipitation is carried out to prepare a co-precipitate precursor with a core-shell structure; by controlling the stirring time, composite precursors with different coating thicknesses can be prepared.
[0104] (3) The composite precursor obtained in step (2) is washed with deionized water and dried, then mixed with sodium carbonate in a stoichiometric ratio and sintered at high temperature: the sintering temperature is 900℃; the sintering time is 20h; and the sintering atmosphere is air.
[0105] (4) Grind the obtained sintered product to prepare a composite oxide material. The chemical formula and particle thickness parameters are shown in Table 1.
[0106] SEM and EDS images of the cathode material are shown below. Figure 2 The material appears as a large, intact sheet, typical of single-crystal materials.
[0107] The cathode material prepared in Example 1 above is coated with Na y Cu i Fe j Mn k (M2) l After the O2 shell, the composite oxide 2θ shows only two diffraction peaks in the 40-50° range at 41.5° and 45.1°, but no diffraction peak at 43.4°. The disappearance of the 43.4° diffraction peak is due to Na... y Cu i Fe j Mn k (M2) lThe O2 structure itself does not have a diffraction peak at 43.4°, and Na x Ni a Fe b Mn c (M1) d The O2 diffraction peak at 43.4° is relatively weak; however, due to the covering layer, the XRD results show that the 43.4° diffraction peak disappears. Figure 3 ).
[0108] 2. Preparation of the positive electrode sheet
[0109] Weigh the positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride prepared in the previous step, and disperse them in an appropriate amount of N-methylpyrrolidone at a weight ratio of 95:2.5:2.5. Stir thoroughly to form a uniform positive electrode slurry. Coat the positive electrode slurry onto the positive electrode current collector aluminum foil, and then dry, roll, and cut to obtain the positive electrode sheet.
[0110] 3. Preparation of negative electrode sheet
[0111] Weigh out the negative electrode active material hard carbon, conductive agent carbon black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in a weight ratio of 90:2.5:5.0:2.5, disperse them in an appropriate amount of deionized water, and stir thoroughly to form a uniform negative electrode slurry. Coat the negative electrode slurry onto the negative electrode current collector copper foil, and then dry, roll, and cut to obtain the negative electrode sheet.
[0112] 4. Preparation of electrolyte
[0113] Inside the glove box, sodium-ion battery electrolyte was prepared at a concentration of 1 mol / L, using NaPF6 as the sodium salt and (EC+DEC) in a volume ratio of 1:1 as the electrolyte solvent, for later use.
[0114] 5. Preparation of sodium-ion batteries
[0115] The positive electrode, negative electrode, and separator are stacked in sequence, with the separator positioned between the positive and negative electrodes. Then, the electrode tabs are welded and the core is wound. The core is then placed in an aluminum-plastic film packaging bag. Finally, electrolyte is injected, and the battery undergoes vacuum sealing, settling, formation, and shaping processes to produce a sodium-ion battery.
[0116] Examples 4-6: Preparation of Sodium-ion Batteries
[0117] Unlike Examples 1-3, the cathode material is not doped with M1 element, and the particle thickness parameters are different. The preparation method of the cathode material is as follows:
[0118] (1) First, soluble nickel sulfate, ferric sulfate and manganese sulfate are mixed in stoichiometric ratio and added to a solvent to obtain a mixed solution, wherein the stoichiometric ratio of Ni / Fe / Mn is 1:1:1; an appropriate amount of ammonia water is slowly added to the mixed solution while stirring, and the pH value of the solution is 11.5±0.2, to obtain a coprecipitate containing Ni, Fe and Mn; after filtration, it is washed with deionized water and set aside for later use.
[0119] (2) Subsequently, soluble copper sulfate, ferric sulfate and manganese sulfate are mixed in stoichiometric ratio and added to a solvent to obtain a mixed solution, wherein the stoichiometric ratio of Cu / Fe / Mn is 2:4:4 or 2:3:5; the precipitate prepared in step (1) is added, and after stirring and mixing evenly, an appropriate amount of ammonia is added to perform co-precipitation to prepare a coprecipitate precursor with a core-shell structure; by controlling the stirring time, composite precursors with different coating thicknesses can be prepared.
[0120] (3) The composite precursor obtained in step (2) is washed with deionized water and dried, then mixed with sodium carbonate in a stoichiometric ratio and sintered at high temperature: the sintering temperature is 900℃; the sintering time is 20h; and the sintering atmosphere is air.
[0121] (4) Grind the obtained sintered product to prepare a composite oxide material. The chemical formula and particle thickness parameters are shown in Table 1.
[0122] Comparative Example 1: Preparation of Sodium-ion Battery
[0123] Unlike Example 1, the cathode material is not doped with M1 element and does not include a shell structure. The preparation method of the cathode material is as follows:
[0124] (1) First, soluble nickel sulfate, ferric sulfate and manganese sulfate are mixed in stoichiometric ratio and added to a solvent to obtain a mixed solution, wherein the stoichiometric ratio of Ni / Fe / Mn is 1:1:1; an appropriate amount of ammonia water is slowly added to the mixed solution while stirring, and the pH value of the solution is 11.5±0.2, to obtain a coprecipitate containing Ni, Fe and Mn; after filtration, it is washed with deionized water and set aside for later use.
[0125] (2) The precursor obtained in step (1) is washed with deionized water and dried, and then mixed with sodium carbonate in a stoichiometric ratio and sintered at high temperature: the sintering temperature is 900℃; the sintering time is 20h; and the sintering atmosphere is air.
[0126] (3) The sintered product was ground to prepare a composite oxide material. The chemical formula and particle parameters are shown in Table 1.
[0127] The XRD pattern of the cathode material (without coating) prepared above is as follows: Figure 4 As shown. By Figure 4 It can be seen that when the cathode material is not coated with a copper-based oxide shell, 2θ has three diffraction peaks in the range of 40-50°, namely 41.5°, 43.4° and 45.1°.
[0128] Comparative Example 2: Preparation of Sodium-ion Batteries
[0129] Unlike Example 1, the shell thickness parameters of the cathode material particles are different. The chemical formula and particle thickness parameters of the composite oxide material are shown in Table 1.
[0130] Comparative Example 3: Preparation of Sodium-ion Batteries
[0131] Unlike Example 1, the cathode material particle thickness parameters are different. The chemical formula and particle thickness parameters of the composite oxide material are shown in Table 1.
[0132] Table 1. Cathode Materials of Examples and Comparative Examples
[0133]
[0134] Battery performance test
[0135] 1. Slurry stability test
[0136] Weigh the positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride prepared in Examples 1-6 and Comparative Examples 1-3, and disperse them in an appropriate amount of N-methylpyrrolidone at a weight ratio of 95:2.5:2.5. Stir thoroughly to form a uniform positive electrode slurry. Store in a dry room with a humidity of 15%, and test the viscosity of the slurry every 12 hours. Measure the viscosity at 12 / 24 / 36 / 48 hours to compare and analyze the slurry stability.
[0137] 2. Capacity Performance Test
[0138] Electrochemical tests were conducted in a glove box using the positive electrode and sodium metal negative electrode of Examples 1-6 and Comparative Examples 1-3, glass fiber separator, and 1 mol / L NaPF6 / (EC+DEC) electrolyte (volume ratio 1:1).
[0139] The performance testing process for button batteries is as follows: the test temperature is 25℃, the voltage range is 2.0~4.0V, and the charge and discharge rate is 0.5C. The specific capacity of the first charge is the specific capacity of the material.
[0140] 3. Full battery room temperature cycle life test
[0141] The sodium-ion batteries of Examples 1-6 and Comparative Examples 1-3 were placed at 25°C and charged at a constant current of 0.5C to the upper limit voltage (4.0V), then charged at a constant voltage of 4.0V to 0.05C, and allowed to rest for 5 minutes; then discharged at a constant current of 0.5C to 1.5V, and allowed to rest for 5 minutes. This constitutes one charge-discharge cycle. This charging / discharging process was repeated, and the ratio of the discharge capacity after the 100th cycle to the discharge capacity after the third cycle was recorded, which is the capacity retention rate after 100 cycles.
[0142] The test results are as follows:
[0143] Table 2. Characteristic parameters of the cathode materials and rate performance test results of the batteries in the examples and comparative examples.
[0144]
[0145] As can be seen from the comparison between Examples 1-3 and Comparative Example 1, after coating with copper-based oxide, the specific capacity of the material is close to that of pure nickel-based oxide. Moreover, after coating with copper-based oxide, the stability of the slurry is significantly improved, and the cycle stability of the battery is significantly improved.
[0146] As can be seen from the comparison of Examples 1-3 and Comparative Examples 2 and 3, when the coating layer thickness is too large, the stability of the slurry is significantly improved. However, due to the low sodium storage capacity of the coating layer, the overall specific capacity is relatively low. Therefore, it is necessary to design a coating layer of appropriate thickness to improve the comprehensive performance of the material.
[0147] Comparing Examples 3 and 4 reveals that doping with suitable elements can improve the air stability and structural stability of the material, resulting in improved slurry stability and cycle stability. This is beneficial for improving the overall performance of the cathode material.
[0148] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that, The cathode material has a core-shell structure, including a core and a shell, wherein the core comprises a nickel-based oxide as shown in Formula I: Na x Ni a Fe b Mn c (M1) d O 2 Formula I Where, 0.7≤ x ≤1.0, 0< a <1, 0< b <1, 0< c <1, 0≤ d <0.1; M1 is selected from one or more of Mg, Zn, Co, Ca, Ba, Sr, Al, B, Cr, V, Zr, Ti, Sn, Mo, Ru, Si, Sb, Nb, and Te; The shell comprises a copper-based oxide as shown in Formula II: Na y Cu i Fe j Mn k (M2) l O 2 Formula II Where, 0.6≤ y ≤1.0, 0< i <1, 0< j <1, 0< k <1, 0≤ l <0.1; M2 is selected from one or more of Mg, Zn, Co, Ca, Ba, Sr, Al, B, Cr, V, Zr, Ti, Sn, Mo, Ru, Si, Sb, Nb, and Te; In X-ray diffraction analysis, the cathode material has two diffraction peaks at 2θ of 40°–42.5° and 44°–46°. The thickness of the shell is 0.1 ~ 1.5 μm.
2. The cathode material according to claim 1, characterized in that, a , b , c , d , i , j , k , l The following relationship must be satisfied: a + b + c + d =1, and / or, i + j + k + l =1.
3. The cathode material according to claim 1, characterized in that, The median particle size D50 of the cathode material particles is 5~20 μm.
4. The cathode material according to claim 3, characterized in that, The median particle size D50 of the cathode material particles is 5~10 μm.
5. The positive electrode material according to claim 1, characterized in that, The thickness of the shell is 1% to 30% of the radius of the cathode material particles.
6. The positive electrode material according to claim 5, characterized in that, The thickness of the shell layer is 1% to 20% of the radius of the cathode material particles.
7. The cathode material according to claim 6, characterized in that, The thickness of the shell layer is 1% to 5% of the radius of the cathode material particles.
8. The positive electrode material according to claim 1, characterized in that, The cathode material includes monocrystalline and / or polycrystalline materials; And / or, the cathode material does not have a diffraction peak at 2θ of 42.5° to 44°.
9. The cathode material according to any one of claims 1-8, characterized in that, The positive electrode material has a powder conductivity of 1.0E-07 ~ 1.0E-05 S / cm at a pressure of 50 MPa.
10. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1-9.
11. A sodium-ion battery, characterized in that, The sodium-ion battery includes the positive electrode material according to any one of claims 1-9, and / or the positive electrode sheet according to claim 10; The negative electrode active material of the sodium-ion battery includes hard carbon; The average particle size Dv50 of the hard carbon is 5~15 μm.
Citation Information
Patent Citations
Composite positive electrode material and preparation method thereof
CN113991079A